(Epi)genetic Inheritance in Schistosoma mansoni: A Systems Approach - Gilda Padalino (Trends in Parasitology, 2017)
The G×E concept, in which genotype × environment interactions bring about the phenotype, is widely used to describe biological phenomena. We propose to extend the initial notion of the concept, replacing G by ‘inheritance system’. This system, comprised of both genome and epigenome components, collectively interacts with the environment to shape the development of a phenotype. In the case of the human blood fluke Schistosoma mansoni, responsible for intestinal bilharzia, the phenotypic trait that is most relevant to global health is infection success. Taking a systems biology view we show how genetic and epigenetic interactions result in ephemeral, but also heritable, phenotypic variations that are important for infection success.